2009
DOI: 10.1007/s00384-009-0643-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cyclooxygenase inhibition on anastomotic healing following large bowel resection in a rabbit model—a randomized, blinded, placebo-controlled trial

Abstract: The application of Valdecoxib does not influence anastomotic healing or new vessel formation in the anastomotic region following large bowel resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0
4

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 33 publications
2
13
0
4
Order By: Relevance
“…Recently, non‐steroidal anti‐inflammatory drugs (NSAIDs) have been suggested as a potential factor in the development of anastomotic leakage8–15. NSAIDs are increasingly being used in fast‐track surgery programmes to optimize pain control and to reduce opioid usage16, 17.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, non‐steroidal anti‐inflammatory drugs (NSAIDs) have been suggested as a potential factor in the development of anastomotic leakage8–15. NSAIDs are increasingly being used in fast‐track surgery programmes to optimize pain control and to reduce opioid usage16, 17.…”
Section: Introductionmentioning
confidence: 99%
“…However, inhibition of cyclo‐oxygenase (COX) interferes with normal processes important for wound repair and healing of intestinal anastomoses20. Experimental studies have shown inferior anastomotic healing following treatment with NSAIDs8–13. Two retrospective clinical studies reported a potential detrimental effect of NSAIDs on anastomotic leakage14, 15.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, retrospective studies [5,6,7] have drawn attention to the possible detrimental effects of the NSAIDs on the anastomotic leakage rate after colorectal resection. The underlying mechanisms have been investigated in several experimental studies, but with conflicting results [8,9,10,11,12,13]. Considerable variation in dosage can explain the different results.…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that the COX-2 level was indeed significantly reduced without clearly impacting on breaking strength of the colonic anastomoses or incisional wounds. In a recent study, Neuss et al [25] also failed to show a detrimental effect of NSAID on breaking strength of experimental colonic anastomoses. NSAID doses varied greatly in the previous studies showing detrimental effects of COX-2 inhibition [7,8,9,17].…”
Section: Discussionmentioning
confidence: 99%